3 3D echocardiography-derived indices of left ventricular function and structure predict long-term mortality differently in men and women: the Southall And Brent Revisited (SABRE) study. (May 2019) - Al Saikhan, Lamia; Park, Chloe; Tillin, Therese; Mayet, Jamil; Chaturvedi, Nish; Hughes, Alun
Abstract : Background: Three-dimensional echocardiography (3DE)-derived indices of left ventricular (LV) structure and function predict mortality in various patient groups, although studies are limited. However, whether these indices equally predict mortality in the general population is unknown. Further, whether known sex-differences in cardiac structure and function modify the relationship between these indices and subsequent death is uncertain. Purpose: We therefore sought to examine the associations between 3DE-derived LV ejection fraction (LVEF), volumes and remodelling, and all-cause mortality in a general population and to investigate whether this relationship is modified by sex. Methods: A total of 910 individuals (age, 69.7±6.2 years; 77.7%% male) from the SABRE study, the UK-largest tri-ethnic community cohort, underwent a heath examination including comprehensive transthoracic echocardiography. Full volume 3D LV datasets acquired over 4 sub-volumes were obtained using a matrix-array transducer, and were analysed offline using Qlab advanced, v7.0. The association between 3D-derived LVEF, body surface area indexed end-diastolic volume (iEDV) and end-systolic volume (iESV), and LV remodelling index (LVRI, the ratio of LV mass and EDV) and risk of all-cause mortality were determined using Cox proportional hazards models. Results: Over a median follow-up of 8 years, 120 participants (13.1%) died. Overall, lower 3D LVEF, and higher 3D iEDV and iESV were associated with increased risk of all-cause mortality (table 1a 1b). However, sex modified the associations between volume indices and LVRI with all-cause mortality; hence we present sex-specific results in table 1. After multivariable adjustment for age, ethnicity, systolic blood pressure, antihypertensive medications, cholesterol: HDL ratio, diabetes, body mass index, smoking and history of coronary heart disease, per SD change, decrease in LVRI and LVEF, and increase in volumes were independently associated with increased risk of mortality in men (figure 1, table 1a 1b). However, associations between volume indices, LVRI and, to a lesser extent, LVEF, and mortality were reversed in women (figure 1, table 1a 1b): fully adjusted hazard ratios (95% CI): EDV: men:1.22(1.0, 1.4), women: 0.55(0.28, 1.1), ESV: men: 1, 31(1.10, 1.60), women: 0.59(0.34, 1.0), LVRI: men: 0.79(0.65, 0.98), women: 1.40(0.88, 2.2), LVEF: men: 0.81(0.67, 0.97), women: 1.31(0.69, 2.5). Although numbers of women are small, effect sizes indicated that lower volumes and higher LVRI were associated with higher risk of all-cause mortality in women. Conclusion: In the general population, 3DE-derived LVEF, volumes and remodelling predict the long-term risk of all-mortality, independent of clinical confounders and cardiovascular risk factors strongly in men. However the direction of association for volumes and remodelling measures is reversed in women suggesting that sex-differences in cardiac structure and function seem to be associated differently with the risk of all-cause mortality. Conflict of Interest: N/A